APLIKASI E GOVERNMENT DAN DAMPAKNYA STUDI KASUS KABUPATEN SRAGEN - Abdul Hamid (Universitas Sultan Ageng Tirtayasa, 2010)
Good Governance is one of the most importance issue in Indonesia post New Order era. One of the ways to applied it to practical world is use an Information Technology (IT) to make public service better. IT application in government, well known as e government, can support government to make a citizen as a consumer get a faster and sure service. Sragen is one of local governments in Indonesia that applied IT in order to support government’s functions. E Government application made a best impact like:public service that most fast and efficient and good climate in investation. This research use a qualitative method to knowing what is the impact of IT application in Government function.